Tunable electronic and magnetic properties of Cr2Ge2Te6 monolayer by organic molecular adsorption. (20th August 2022) - Zhang, Jieqi; Zhang, Chao; Ren, Kai; Lin, Xiuling; Cui, Zhen
Abstract: Recently, two-dimensional materials are widely concerned because of their novel physical properties. Cr2 Ge2 Te6 (CGT) has been studied extensively due to its intrinsic ferromagnetism and ferromagnetic order. In this investigation, the electronic and magnetic performances of organic molecules (TCNE, TCNQ and TTF) adsorbed on CGT monolayer were studied based on the first-principles calculations systematically. The results demonstrate that the CGT presents pronounced tunable electronic and magnetic properties by the adsorption of these macromolecules. Furthermore, the Curie temperature of CGT monolayer can be enhanced significantly by the TTF adsorption. This work can provide a magnetic regulation method for CGT and explore the promising applications of the CGT for spin devices.